Horizontal Plasmid Transfer by Transformation in Escherichia coli: Environmental Factors and Possible Mechanisms - Hasegawa, Haruka; Suzuki, Erika; Maeda, Sumio (Frontiers in Microbiology, 2018)
Transformation is one mode of horizontal gene transfer (HGT) in bacteria, wherein extracellular naked DNA is taken up by cells that have developed genetic competence. Sensitivity to DNase, which degrades naked DNA, is the key to distinguishing transformation from the DNase-resistant HGT mechanisms. In general, Escherichia coli is not believed to be naturally transformable; it develops high competence only under artificial conditions, including exposure to high Ca2+ concentrations. However, E. coli can reportedly express modest competence under certain conditions that are feasible in natural environments outside laboratory. In addition, recent data suggest that environmental factors influence multiple routes of transformation. In this mini review, we (1) summarize our studies on transformation-based HGT using E. coli experimental systems and (2) discuss the possible occurrence of transformation via multiple mechanisms in the environment and its possible impact on the spread of antibiotic resistance genes.